2013
DOI: 10.1002/art.38213
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Carboxypeptidase B Serves as a Protective Mediator in Osteoarthritis

Abstract: Objective We previously demonstrated that carboxypeptidase B (CPB) protects against joint erosion in rheumatoid arthritis by inactivating complement component C5a. We also found that levels of CPB are abnormally high in the synovial fluid of individuals with another joint disease, osteoarthritis (OA). In this study, we investigated whether CPB has a role in the pathogenesis of OA. Methods We compared the development of OA in CPB-deficient (Cpb2−/−) mice and wild-type mice by subjecting them to medial menisce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…In contrast, collagen IX, properdin, and CD59 can act as inhibitors of complement (107). In recent studies, mice with impaired ability to generate the complement membrane attack complex (MAC) were partially spared from the development of OA, showing direct evidence of role of complement system in OA pathogenesis (108). However, the way complement deposition occur in joint synovium of OA, and the role of the complement cascade in the pathogenesis remain to be precisely determined.…”
Section: Correlation Between Synovitis and Oamentioning
confidence: 94%
“…In contrast, collagen IX, properdin, and CD59 can act as inhibitors of complement (107). In recent studies, mice with impaired ability to generate the complement membrane attack complex (MAC) were partially spared from the development of OA, showing direct evidence of role of complement system in OA pathogenesis (108). However, the way complement deposition occur in joint synovium of OA, and the role of the complement cascade in the pathogenesis remain to be precisely determined.…”
Section: Correlation Between Synovitis and Oamentioning
confidence: 94%
“…Pharmacologically blocking the complement system by CR2-fH, a fusion protein of a complement receptor and the naturally occurring inhibitor factor H, was associated with less severe joint damage (35). The same group showed that carboxypeptidase B (CPB) appeared to have a protective role in OA by inhibiting the complement system (55). Similar to their previous findings (35), in a medial menisectomy OA model, mice that were deficient for CPB showed more cartilage degeneration, osteophyte formation and synovitis than wild-type mice (55).…”
Section: The Complement Systemmentioning
confidence: 99%
“…The same group showed that carboxypeptidase B (CPB) appeared to have a protective role in OA by inhibiting the complement system (55). Similar to their previous findings (35), in a medial menisectomy OA model, mice that were deficient for CPB showed more cartilage degeneration, osteophyte formation and synovitis than wild-type mice (55). In addition, they found that levels of CPB correlated to levels of MAC in the synovial fluid of patients with OA; suggesting that CPB has an anti-inflammatory role in the joint (55).…”
Section: The Complement Systemmentioning
confidence: 99%
“…Indeed, the vulnerability may arise when individuals with altered or compromised joint biology sustain injury or altered loading. 12, 33 Thus a simple “wear and tear” explanation does not provide a sufficient basis to move forward with new prevention modalities or new methods for early detection of OA as a better understanding of OA at a systems level is needed.…”
Section: A Systems View Of Oa Risk Factorsmentioning
confidence: 99%